Lane-Emden equations perturbed by nonhomogeneous potential in the super critical case - Ma Y. (2021)
Y. Ma is supported by Key R&D plan of Jiangxi Province, No:20181ACE50029, Y. Wang is supported by NNSF of China, No:12001252 and 12071189, by the Jiangxi Provincial Natural Science Foundation, No:20202ACBL201001 and 20202BAB201005, by the Science and Technology Research Project of Jiangxi Provincial Department of Education, No: 200325 and 200307, C. Torres was partially supported by CONCYTEC, Peru, 379-2019-FONDECYT “ASPECTOS CUALITATIVOS DE ECUACIONES NO-LOCALES Y APLICACIONES”